2009
DOI: 10.11646/zootaxa.2062.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic revision of the Asian endemic subgenus Physocrema of the genus Crematogaster (Hymenoptera: Formicidae)

Abstract: The subgenus Physocrema of the genus Crematogaster is revised. Twelve species are recognized in the subgenus, of which two are new to science: C. (Physocrema) tanakai sp. nov. and C. (P.) yamanei sp. nov. An identification key based on the worker caste is provided. Taxonomic relationships between C. (P.) difformis and similar species are clarified. Crematogaster (P.) vacca Forel 1911 is raised to species level. The following new synonymies are proposed: C. (P.) inflata F. Smith 1857 = C. (P.) moorei Donisthorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Cell counts for the metapleural gland in members of the congeners Crematogaster clariventris M ayr 1895 and Crematogaster depressa L atreille 1802 yield a total of 350 and 400 cells, respectively, which is among the highest known number among myrmicine ants (Fanfani & Giovannotti 1994). Members of the congeneric Crematogaster sewardi , which also belongs to the Physocrema group, also have enlarged metapleural glands (Maschwitz 1974; Hosoishi & Ogata 2009), but with total cell numbers of 747 and 774 in the two workers checked, their size is only half that of the glands of C. inflata . Maschwitz (1974) reported that the metapleural glands of C. sewardi (misidentified as Crematogaster difformis ) show the usual antibiotic function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell counts for the metapleural gland in members of the congeners Crematogaster clariventris M ayr 1895 and Crematogaster depressa L atreille 1802 yield a total of 350 and 400 cells, respectively, which is among the highest known number among myrmicine ants (Fanfani & Giovannotti 1994). Members of the congeneric Crematogaster sewardi , which also belongs to the Physocrema group, also have enlarged metapleural glands (Maschwitz 1974; Hosoishi & Ogata 2009), but with total cell numbers of 747 and 774 in the two workers checked, their size is only half that of the glands of C. inflata . Maschwitz (1974) reported that the metapleural glands of C. sewardi (misidentified as Crematogaster difformis ) show the usual antibiotic function.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of the number of secretory cells was carried out by counting the cumulative number of cells occurring in serial sections through the entire thorax at 30‐μm intervals (which is the average cell diameter). Workers of Crematogaster sewardi (which, like C. inflata , belongs to the Physocrema group: Hosoishi & Ogata 2009), collected in the Bogor Botanical Gardens, Indonesia, were prepared the same way for comparison of the number of secretory cells in their metapleural glands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crematogaster ants in the subgenus Physocrema have hypertrophied MGs (Janet, 1898 b ; Donisthorpe, 1941; Hosoishi & Ogata, 2008, 2009), and MG secretions of Crematogaster difformis and Crematogaster inflata contain a mixture of phenolic compounds that are noxious to predators (Attygalle et al , 1989; Jones et al , 2005). When C. ( Physocrema ) inflata workers are attacked, they expel from the MG opening a droplet of a whitish, viscous, sticky secretion which they can retract back into the MG (Maschwitz, 1974; Buschinger & Maschwitz, 1984).…”
Section: Functions Of the Metapleural Glandmentioning
confidence: 99%
“…The genus Crematogaster is one of the most diverse ant genera, particularly in the tropics (Hölldobler & Wilson, ). The regional‐scale taxonomy and systematics of the genus, which includes 487 valid species‐level names (Bolton, ) in two subgenera (Blaimer, 2012c, d), have received considerable attention in recent years (Longino, ; Hosoishi & Ogata, , ; Blaimer, , , ).…”
Section: Introductionmentioning
confidence: 99%